The Association of Neurosurgeons in the German Democratic Republic and its First Congresses in Divided Germany - Synowitz, Michael; Rosenow, Detlef; Synowitz, Hans-Joachim (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
The German Society of Neurosurgery (DGNC) was founded in Bonn in 1950 and saw itself as the all-German representation of neurosurgeons. The development of neurosurgery in divided Germany was different in each case as part of a system and was not unaffected by the confrontation between the two blocs (cold war), which also had a negative impact on the field of science. Thus, early on, restrictions on intra-German travel from the East made normal relations difficult. But travel restrictions also came from the West, where an Allied Travel Office in West Berlin decided whether an East German could enter a North Atlantic Treaty Organization (NATO) country. Nevertheless, it was possible that Georg Merrem from Leipzig took over the second chairmanship of the board of the DGNC of the election period from 1960 to 1962 and eight individual memberships of German Democratic Republic (GDR) neurosurgeons were still tolerated by the state side. The construction of the Berlin Wall on August 13, 1961 meant that these connections also collapsed. Merrem, at that time the only full professor of neurosurgery in the GDR, founded the “Association of Neurosurgeons in the GDR” in 1962 in agreement with the state authorities. With the foundation of a GDR neurosurgeons' society, the demarcation from the DGNC desired by the state was visibly accomplished. There were no official relations between the two neurosurgical societies. During the period of its existence until 1990, the entire work of the East German society was under the guidance and control of state institutions, which in turn derived their work from the guidelines of the party and the decisions of the council of ministers. Using the example of the congress activities of the first 5 years after the Wall was built, we show this dependence on state institutions. It extends from congress planning to reporting. With available figures of participating speakers from West Germany and other countries, it is demonstrated for the individual congresses in Leipzig, Magdeburg, and Erfurt that the German–German connection was continued despite all adverse circumstances. The presence of West German colleagues, who were not deterred from attending the congress even by the construction of the Berlin Wall, can be seen as a visible expression of an unbroken togetherness. However, already in 1967, the party and the council of ministers passed the resolution “On the organization of work in the field of science and culture of the GDR to West Germany as well as West Berlin.” This regulated membership, the associated travel, and the conditions for publications in West German journals. Among other things, this directive prohibited membership in scientific societies, including the DGNC, based in West Germany. The organization of its own congresses took on a special significance because a congress visit from East to West was regulated by the state and thus only possible in isolated cases.
Keywords: GDR; neurosurgery; congress; cold war; Berlin wall